Synthesis of polydopamine‐functionalized magnetic graphene and carbon nanotubes hybrid nanocomposites as an adsorbent for the fast determination of 16 priority polycyclic aromatic hydrocarbons in aqueous samples. Issue 8 (6th February 2018) - Chen, Kun; Jin, Rongrong; Luo, Chen; Song, Guoxin; Hu, Yaoming; Cheng, Hefa
Abstract: A novel adsorbent made of polydopamine‐functionalized magnetic graphene and carbon nanotubes hybrid nanocomposite was synthesized and applied to determine 16 priority polycyclic aromatic hydrocarbons by magnetic solid phase extraction in water samples. FTIR spectroscopy, transmission electron microscopy, scanning electron microscopy, and Raman spectroscopy consistently indicate that the synthesized adsorbents are made of core–shell nanoparticles well dispersed on the surface of graphene and carbon nanotubes. The major factors affecting the extraction efficiency, including the pH value of samples, the amount of adsorbent, adsorption time and desorption time, type and volume of desorption solvent, were systematically optimized. Under the optimum extraction conditions, a linear response was obtained for polycyclic aromatic hydrocarbons between concentrations of 10 and 500 ng/L with the correlation coefficients ranging from 0.9958 to 0.9989, and the limits of detection (S/N = 3) were between 0.1 and 3.0 ng/L. Satisfactory results were also obtained when applying these magnetic graphene/carbon nanotubes/polydopamine hybrid nanocomposites to detect polycyclic aromatic hydrocarbons in several environmental aqueous samples.